2002
DOI: 10.1210/jc.2002-020343
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I/IGF-Binding Protein-3 Combination Improves Insulin Resistance By GH-Dependent and Independent Mechanisms

Abstract: IGF-I has been shown to enhance insulin sensitivity in patients with type I and type II diabetes. IGF-I suppresses GH, and this raises the question of whether its ability to enhance insulin sensitivity is mediated solely through a reduction in GH's antiinsulin actions. This study was conducted to determine whether administration of a GH receptor antagonist to patients with acromegaly and insulin resistance would result in improvement in insulin sensitivity and whether IGF-I had any additional insulin-sensitizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…insulin sensitization is improved by treatment with agents that block GH secretion in a substantial number of patients (51,52). In a recent study by O'Connell and Clemmons, a GHR antagonist was given to acromegalic patients for 6 months to block GH action (53). This study clearly demonstrated that GHR antagonist treatment significantly improved insulin sensitivity.…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…insulin sensitization is improved by treatment with agents that block GH secretion in a substantial number of patients (51,52). In a recent study by O'Connell and Clemmons, a GHR antagonist was given to acromegalic patients for 6 months to block GH action (53). This study clearly demonstrated that GHR antagonist treatment significantly improved insulin sensitivity.…”
Section: Figurementioning
confidence: 81%
“…This study clearly demonstrated that GHR antagonist treatment significantly improved insulin sensitivity. Addition of IGF-1 in combination with the GHR antagonist resulted in substantially greater improvement in the insulin sensitivity, suggesting that IGF-1 exerts additional effects on insulin sensitivity that are not mediated through suppression of GH action (53). GH plays a role in the regulation of lipolysis and lipogenesis, as well as in the differentiation of preadipocytes (54,55).…”
Section: Figurementioning
confidence: 99%
“…IGF-1 administration has also been demonstrated to improve insulin sensitivity in both type 1 diabetic and type 2 diabetic patients (28,29). In another clinical study involving patients with acromegaly (30), combined treatment with GH receptor antagonist plus IGF-1/IGFBP-3 was found to be more effective in improving insulin sensitivity than treatment with GH receptor antagonist itself, suggesting that the insulin-sensitizing effect of IGF-1 is partly independent of its ability to suppress GH secretion (30).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of a GH antagonist to diabetics results in relative restoration of normal carbohydrate metabolism but does not completely ameliorate the defect in insulin sensitivity (10). Similarly, administration of a GH receptor antagonist to acromegalics improves insulin sensitivity but does not restore it to the normal range (11).…”
Section: Food Intake and Gh Regulate Insulin-like Peptide Secretionmentioning
confidence: 99%